Characteristics of children with sporadic hemolytic uremic syndrome in a single Northern California center - Oh, Gia; Lau, Keith K. (International urology and nephrology, 2012)
Purpose Hemolytic uremic syndrome (HUS) is a frequent cause of acute kidney injury in children. The aim of this study is to describe our experience at a Northern California center. Methods Medical records of children suffered from HUS (08/99 to 03/09) at University of California Davis Medical Center were reviewed. Results Forty-six children (70% girls) were studied, and their median age was 3.5 years. Diarrhea was a presenting symptom in 42 subjects (91%), and hematochezia was present in 31 children (67%). Escherichia coli 0157:H7 was isolated in 20 patients (44%). Thirteen subjects (28%) underwent dialysis for a median of 7 days during their hospitalization. Follow-up was achieved in 36 patients (78.3%) for a median of 16 months. One patient required angiotensin-converting enzyme (ACE) inhibitor for proteinuria but none was on dialysis. Conclusions In our cohort in children with HUS in a single Californian center, long-term complications were uncommon during a median follow-up time of 16 months.